Drugs, victims and race : the politics of drug control - Kalunta-Crumpton, Anita, 1962- (Waterside Press ; Distributed in North America by International Specialized Book Services (ISBS), 2006)
A book that offers a fresh perspective on discourse around the 'drug problem' - in which Anita Kalunta-Crumpton explores common but frequently misleading themes concerning an aspect of criminal justice that know no racial, ethnic, gender, class, age, geographical or other barriers. She also provides an outline of UK drugs strategy from its class-oriented beginnings in the nineteenth century - through later expansion and pre-occupation with explanations based around race - up until the present day, causing her to ask: Who are the real victims of drugs, drug trafficking and drug supply? The book examines the 'drug problem' in the context of UK strategies and as a global phenomenon. Set against the backdrop of race and the politics of drug control, it looks at a range of events and issues from the supply end of the drugs chain through enforcement and court proceedings to treatment approaches re addicts and other drug users. Anita Kalunta-Crumpton also goes beyond myths, stereotypes and assumptions to look at the real life issues and social characteristics that affect the trafficking, supply and use of drugs.